242 Safer journeys for primary students in LMICs: effectiveness of multi-pronged model. (20th November 2022) - Bui, Quyen; Nguyen, Le; Sidik, Mirjam
Abstract : In Thailand and Vietnam, nearly 4, 200 children are killed on the road annually, most of them (99%) being pedestrians or two-wheeler passengers (IHME, 2019). In response, AIP Foundation has utilized a multi-pronged approach model across different projects targeting 26 primary schools in the two countries to provide safer school zones, equipment and deeper road safety understanding to students. Over 2015–2021, these projects distributed 6, 476 high-quality helmets, installed 21 low-cost road modifications around school zones and delivered 16, 498 primary students with intensive road safety education. The effectiveness of this model was determined using unannounced filmed helmet and pedestrian observations to capture behavior changes, and self-reported questionnaires to test road safety knowledge among targeted students. Besides, the iRAP Star Rating for Schools (SR4S) tool was applied to measure the risk children are exposed to around school zones. Comparing prior- and post-intervention results, the standard helmet use rates among students experienced a remarkable change, from 10% to 59%. The percentage of child pedestrians using the zebra crossings and sidewalks correctly increased by an average 59% and 18%, respectively. The rate of students with excellent road safety knowledge raised from 9.8% to 59.6%. The schools that were rated 1–2 stars (least safe) by SR4S at baseline, were upgraded to 4–5 stars (safest). Findings suggest this model has proved itself as a cost-effective and successful life-saving intervention that can contribute to the SDGs and should be replicated in other low- and middle-income countries.